Possible states of charge carriers in thin multilayered superconductive ceramics - Jovan P. Šetrajčić; Siniša M. Vučenović; Stevo K. Jaćimovski (Zaštita Materijala)
This paper analyzes behavior (spectra and states) of the elementary charge carriers in anisotropic perovskite structures, such as modern superconducting ceramics. Translational symmetry of the atom (ion) distribution of the electron (or hole) system is broken by atomic/ionic/molecular sputtering and doping, as well as due to existence of two boundary surfaces. This is a charge carrier's model of high-temperature superconductors in which the observed symmetry breaking orthogonal to CuO planes was treated as a perturbation. The single-particle fermion's wave functions and the possible energies of charge carriers were determined.